Graphene platelets/aluminium nitride metacomposites with double percolation property of thermal and electrical conductivity. Issue 14 (November 2018) - Yin, Rui; Zhang, Yubai; Zhao, Wen; Huang, Xiaoshuai; Li, Xiaomin; Qian, Lei
Abstract: Graphene platelets/aluminium nitride (GPLs/AlN) metacomposites with double percolation property of thermal and electrical conductivity were successfully fabricated by spark plasma sintering. Microstructures and phase composition of the GPLs/AlN metacomposites were investigated by field emission scanning electron microscopy, X-ray diffraction and Raman spectroscopy. With increase of the GPLs contents, the double percolation property of thermal (19.27 wt% GPL) and electrical conductivity (19.03 wt% GPL) was found. Moreover, the negative permittivity behavior was also observed when the GPLs content reached 19.50 wt%, which was attributed to the formation of continuous GPLs networks. Finally, the equivalent circuit models were used to analyze the negative permittivity behavior. As the reactance ( Z′′ ) converted from negative to positive, the inductors were introduced into the equivalent circuit models, and the GPLs/AlN metacomposites went through the capacitive-inductive transition with the increasing GPLs content, corresponding to the negative permittivity behavior.